Understanding amyloid light chain cardiac amyloidosis: a case study emphasising integrated diagnostic techniques - Chaudhary, Mahima; Alam, Mohammad Altamash; Qiu, Yuangang; Pan, Yanyun (International Journal of Research in Medical Sciences, 2025)
Cardiac amyloidosis, a manifestation of systemic amyloidosis, presents diagnostic challenges due to diverse clinical presentations. A 56-year-old woman with a history of hypertension presented with recurrent chest tightness, palpitations, decreased exercise tolerance, and nocturnal dyspnea. Diagnostic workup revealed reduced left ventricular function, thickened interventricular septum, and left atrial enlargement on echocardiography and electrocardiogram. Immunohistochemical staining confirmed AL amyloidosis in bone marrow biopsy specimens. Treatment involved supportive care and chemotherapy for plasma cell dyscrasia. Prompt identification and intervention for AL amyloidosis are crucial, highlighting the diagnostic role of electrocardiograms and echocardiograms. Management strategies included supportive care and chemotherapy for plasma cell dyscrasia. This case underscores the significance of timely recognition and intervention for cardiac amyloidosis, contributing to improved understanding and management approaches.